Tobacco in prisons: a focus group study. Issue 3 (2nd February 2009) - Richmond, R; Butler, T; Wilhelm, K; Wodak, A; Cunningham, M; Anderson, I
Abstract : Objective: To examine the role of tobacco use in prison and possible influences of the prison environment on smoking among inmates in the context of developing inmate smoking cessation programmes. Method: Qualitative study based on seven focus groups with prisoners and ex-prisoners. Settings: A maximum security prison in rural New South Wales (NSW), Australia, and a community justice restorative centre and accommodation service for ex-prisoners in Sydney, NSW, Australia. Participants: 40 participants (28 men and 12 women) comprising nine prisoners (including four Indigenous inmates) and 31 ex-prisoners. Results: Prisoners reported that tobacco serves as a de facto currency in correctional settings and can be exchanged for goods, used to pay debts and for gambling. Smoking helps manage the stressful situations such as transfers, court appearances and prison visits. Inmate smoking cessation programmes need to address the enmeshment of tobacco in prison life, improve availability of pharmacotherapies (for example, nicotine patches, bupropion) and the quitline (a free telephone helpline providing information on stopping smoking), provide non-smoking cells and areas within prisons, encourage physical activity for inmates and maintain monitoring of smoking cessation status after release. Conclusions: Tobacco is integrally bound up in the prison "culture". Our findings are relevant to inform prison health authorities concerned with improving the health of prisoners, and for support organisations attempting to facilitate smoking cessation both in prison and after release. Smoking cessation programmes in prisons should be tailored to the unique stresses of the prison environment. Programmes need to acknowledge the difficulties of quitting smoking in prison arising from the stresses posed by this setting.